Rapid Access Palliative Radiotherapy Programmes. Issue 11 (November 2020) - Dennis, K.; Harris, G.; Kamel, R.; Barnes, T.; Balboni, T.; Fenton, P.; Rembielak, A.
Abstract: One of the greatest successes of radiotherapy has been its ability to palliate symptoms from advanced and metastatic cancers. Unfortunately, patients face barriers to accessing care and the demand for treatment is rising. Rapid access palliative radiotherapy programmes were created in response to these concerns, and over time they have proliferated and succeeded internationally. This narrative review provides an overview of programmes that have published their experiences, and discusses how they have improved access to care, increased evidence-based practice, met the needs of vulnerable populations, advanced the roles of multidisciplinary team members, collaborated across medical specialties, educated trainees and referring physicians, and developed new treatment platforms using advanced technologies.